1955
DOI: 10.1017/s0022172400000954
|View full text |Cite
|
Sign up to set email alerts
|

Sterilization of Air by Heat

Abstract: SummaryEquipment for the sterilization of air by heat with capacities of 140 l./min., and 1700 l./min. respectively is described. An improved method for testing sterility is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1956
1956
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…For example, even if no contaminants are found in a sample of 1000 colonies examined, there is still a 5 yo chance that the degree of contamination is really as high as 0.3y0. The same considerations apply in any form of sterility testing and are discussed in more detail by Elsworth, Telling & Ford (1955).…”
Section: Maintenance Of P U R I T Y Of Culturementioning
confidence: 99%
“…For example, even if no contaminants are found in a sample of 1000 colonies examined, there is still a 5 yo chance that the degree of contamination is really as high as 0.3y0. The same considerations apply in any form of sterility testing and are discussed in more detail by Elsworth, Telling & Ford (1955).…”
Section: Maintenance Of P U R I T Y Of Culturementioning
confidence: 99%
“…Continuous thermal sterilization of air is a simple concept that was first introduced in 1950–1960, when the needs for supplying sterile air to biological reactors appeared (Humphrey 1960 ). Elsworth et al ( 1955 ) reported that an air sterilizer operated at 300 °C and a minimum residence time of 1.6 s could reduce the penetration of spores suspended in air to 1 in 470 million. The basic idea of thermal sterilization is to heat the air stream to a sufficiently high temperature (sterilization temperature), and to keep it at that temperature for some time (sterilization time) in order to effectively inactivate the microorganism.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal sterilization is a simple concept that was first introduced in 1950-1960 to satisfy the supply of sterile air to biological reactors. Elsworth et al [16] early reported that heating air at 300˚C for a minimum residence time of 1.6 s could reduce the penetration of spores in the air to 1 in 470 million. Thermal treatment is a robust and proven technique for the destruction of microorganisms in the air, both pathogenic and non-pathogenic.…”
Section: Introductionmentioning
confidence: 99%